Developing Creative Economic Skills of Students through Book-Making Training at the Nurul Al Bantani Islamic Boarding School in Serang City - Amarul, Amarul; Supriatna, Yuda; Nafiudin; Azizah; Jaafar (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2026)
This Community Service Program aims to develop the creative economic skills of students through bouquet-making training at Nurul Al Bantani Islamic Boarding School, Serang City. The program was motivated by the need to enhance students’ practical skills and entrepreneurial capacity as preparation for economic independence in the creative economy era. The implementation method employed a training and hands-on practice approach, including the delivery of creative economy concepts, bouquet-making practice, and assistance in calculating production costs, determining selling prices, and applying simple marketing strategies. The results indicate that students were able to understand and master basic bouquet-making techniques and produce neat, aesthetically pleasing, and marketable products. In addition to improving technical skills, the program also fostered creativity, entrepreneurial interest, and awareness of creative business opportunities within the boarding school environment. This program is expected to serve as a sustainable model for student empowerment and contribute to the economic self-reliance of Islamic boarding schools.